Museu como instrumento de gestão do patrimônio cultural: desenvolvimento do plano museológico no museu antropológico diretor pestana - Cardoso, Luciana Silveira (2014)
The text presented is the result of research of the dissertation to the Graduate Program in Cultural Heritage College of the Federal University of Santa Maria (PPGPPC / UFSM). In this work we will analyze the theme of Management museological institutions, taking as a case study the Anthropology Museum Director Pestana, a private institution maintained by the Foundation for Integration, Development and Education of Northwest State of Rio Grande do Sul. For this research proposes the Situational Diagnosis of Museum and later development of specific programs, however without being developed Projects. We base our look at the guidelines of Law 11.904/2009 that implements the Status of Museums, with the result of this work a proposal for a museum site plan for the institution, considering especially the local realities and possibilities of adjusting it.